2023
DOI: 10.1002/gps.5955
|View full text |Cite
|
Sign up to set email alerts
|

Global assessment, cognitive profile, and characteristics of mild cognitive impairment in Parkinson's disease

Abstract: Background: Cognitive deficits are evident throughout the course of Parkinson's disease (PD), with 24% of patients experiencing subtle cognitive disturbances at the time of diagnosis, and with up to 80% of patients developing PD dementia (PDD) at advanced stages of the disease PD patients with mild cognitive impairment (MCI), an at-risk phenotype of PDD, present with heterogeneous clinical characteristics that complicate the management of PD. Objectives: This study aims to examine the characteristics of PD-MCI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
(131 reference statements)
0
3
0
Order By: Relevance
“…In evaluating cognitive function, MoCA is the most commonly used neuropsychological scale in clinical practice to quickly and easily assess cognitive function. However, it exhibits poor psychological measurement characteristics and low sensitivity and specificity, 28 and as a subjective quantitative measure, it cannot directly reflect changes in neuropathology. In addition, although the diagnostic performance of radiomics model is close to that of a multimodal combinatorial model and can reflect some changes in neuropathology, due to the long course of PD.…”
Section: Discussionmentioning
confidence: 99%
“…In evaluating cognitive function, MoCA is the most commonly used neuropsychological scale in clinical practice to quickly and easily assess cognitive function. However, it exhibits poor psychological measurement characteristics and low sensitivity and specificity, 28 and as a subjective quantitative measure, it cannot directly reflect changes in neuropathology. In addition, although the diagnostic performance of radiomics model is close to that of a multimodal combinatorial model and can reflect some changes in neuropathology, due to the long course of PD.…”
Section: Discussionmentioning
confidence: 99%
“…MCI, a transitional stage between normal cognition and dementia, can occur in the presymptomatic phase of PD; it affects 19–30% of newly diagnosed, untreated (de novo) PD patients and has a frequency ranging from 21% to 70% with a mean of 25.8% [ 25 , 57 , 58 , 59 , 60 , 61 ]. About 30% of de novo PD patients complain of memory issues and are more likely to develop MCI after 2 years follow-up [ 50 ], but other factors, such as anxiety and affective symptoms, may contribute to the progression of cognitive deficits [ 62 , 63 ].…”
Section: Epidemiology Of CI In Pdmentioning
confidence: 99%
“…The cognitive phenotype was heterogenous; the most common subtypes were amnestic and non-amnestic MCI (aMCI, naMCI) single domain (11.3% and 8.9%, respectively) [ 76 ]. More recent studies reported 69.3% PD-MCI, 16% PD with normal cognition (PD-NC) and 14.66% PDD [ 77 ] or 34% PD-MCI with 77.8% impaired in multiple cognitive domains [ 59 ].…”
Section: Epidemiology Of CI In Pdmentioning
confidence: 99%
See 1 more Smart Citation